The credibility of Islamic religious institutional websites in Malaysia - Norhafezah Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study is an attempt to fill the gap in website credibility studies and online religious studies, as these areas seldom link when researching the credibility of Islamic religious websites. The researcher investigates the nature of 13 state-based Islamic institutional religious websites to discover whether these websites are seen as credible, based on a framework of website credibility. Eight media and communication experts were interviewed. The findings suggest that institutional Islamic religious websites have achieved the authority and objectivity features of website credibility. However, the authority of the websites requires that the accuracy, currency and coverage features are upgraded. This study is timely as it contributes to the fields of internet, communication, and religious studies.